THE DISASTER PREPAREDNESS EDUCATIONTHROUGH TRIANGLE ALERT GAME TO INCREASE CHILDREN'S INDEPENDENCE IN TUNAS BANGSA KINDERGARTEN IN DEALING WITH DISASTERS IN COASTAL AREA OF BONANG DISTRICT, DEMAK REGENCY - Yanti, Desy Dwi; Mukminin, Amirul (Jurusan PGPAUD FIP UNNES, 2019)
Disasters cannot be avoided but can be muted if the community has sufficient information about disaster prevention. The lack of information had about what should be done when a disaster occurs, especially for children, makes them vulnerable to disasters. Therefore, education about disaster preparedness is very necessary for early childhood. The purpose of this study is to determine whether there is an influence on the implementation of disaster education through a triangle alert game on children's independence when facing disasters in the coastal area of Bonang District, Demak Regency. Through the triangle alert game, it can be seen whether there are differences in the level of independence of children when facing a disaster. The research method in this research is an experiment. The study uses the one-group pretest-posttest design method.An experiment is carried out in one group without a comparison group. The research instrument with the parameters of independence uses a Likert scale with answers